Inovasi dan Penguatan Ekosistem Fintech Syariah di Indonesia: Studi Kasus Crowdfunding dan P2P Lending Syariah di Indonesia - Elvira Khairunnisa Ibrahim; Muhammad Albahi; Rozi Andrini (OIKONOMIKA : Jurnal Kajian Ekonomi dan Keuangan Syariah, 2025)
Digital transformation has driven significant growth in Indonesia’s Islamic finance industry. Through innovations in financial technology (fintech), Sharia-based financial services have become more inclusive, efficient, and transparent. This study aims to analyze the forms of Sharia financial product innovations based on fintech, particularly in the models of crowdfunding and Sharia peer-to-peer (P2P) lending, as well as to identify the challenges and strategies for strengthening its ecosystem. The research employs a literature review method with a descriptive-comparative approach, drawing from various academic publications, reports from the Financial Services Authority (OJK), and data from the Indonesian Sharia Fintech Association (AFSI). The findings show that Sharia fintech plays a strategic role in expanding access to halal financing for MSMEs through mechanisms such as mudharabah, musyarakah, and qardh hasan. However, challenges remain in the form of low Islamic financial literacy, limited regulations and human resources, and weak public trust in fund management transparency. Strengthening strategies required include regulatory harmonization and contract standardization, enhancement of Sharia digital literacy, technological innovation through blockchain and smart contracts, and cross-sector collaboration among regulators, academics, and industry players. With the implementation of these strategies, Indonesia’s Sharia fintech ecosystem has the potential to become an inclusive, equitable, and sustainable Islamic financial model aligned with the values of maqāṣid al-sharī‘ah.